Clinical Characteristics and Underlying Factors Related to Recovery from Severe Pneumonia in Under-Five Children with or without Malnutrition Treated at Health Care Facilities in Bangladesh - K. A. T. M. Ehsanul Huq; Michiko Moriyama; Ryota Matsuyama; Mohammod Jobayer Chisti; Md Moshiur Rahman; Nur Haque Alam (Children, 2021)
Severe pneumonia with co-morbidity of malnutrition is one of the leading causes of death among children younger than five years of age. We aimed to compare the clinical features related to recovery from severe pneumonia in malnourished and well-nourished under-five children. A significantly lesser proportion of malnourished children compared to well-nourished recovered from rapid breathing (86.5% vs. 90.2%; p = 0.035), chest wall in-drawing (90.5% vs. 93.9%; p = 0.019), and fever (92.2% vs. 95.2%; p = 0.021) on day six after admission to health-care facilities. Malnourished children with severe pneumonia had significantly more rapid breathing (Adjusted Odds Ratio (AOR)) 1.636, 95% Confidence interval (CI) 1.150–2.328 p = 0.006), chest wall in-drawing (AOR 1.698, 95% CI 1.113–2.590, p = 0.014), and fever (AOR 1.700, 95% CI 1.066–2.710, p = 0.026) compared to those in well-nourished children. The study results suggested the lesser disappearance of clinical features among the malnourished children in Bangladesh underscores their vulnerability to severe pneumonia.